2021
DOI: 10.1186/s12903-020-01376-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of children and young adults with maple syrup urine disease in Turkey

Abstract: Background Maple syrup urine disease (MSUD) is an inherited disorder clinically characterized by ketoacidosis, seizures, coma, psychomotor delay, and intellectual disability. The treatment requires a life-long protein-restricted diet, rich in carbohydrates and fats, supplemented with a medical amino acid formula. Diet, oral health and general health influence each other in a vicious cycle. The aim of this study was to investigate the oral health status of children and young adults with MSUD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Fukushima et al, 1986 and Gazit et al, 1989 reported the presence of rampant caries in a 5-year-old girl a 14-year-old boy with classical MSUD respectively [ 18 , 20 ]. Similar findings were reported in a retrospective study from Turkey where Ballikaya et al, 2021 examined 25 children and young adolescents with MSUD and identified dental caries in 72% of the cases [ 17 ]. The mean dmft score was 6.2 and dmfs was 22.26, while the mean DMFT score was 2.66 and DMFS was 5.83.…”
Section: Scoping Reviewsupporting
confidence: 84%
See 4 more Smart Citations
“…Fukushima et al, 1986 and Gazit et al, 1989 reported the presence of rampant caries in a 5-year-old girl a 14-year-old boy with classical MSUD respectively [ 18 , 20 ]. Similar findings were reported in a retrospective study from Turkey where Ballikaya et al, 2021 examined 25 children and young adolescents with MSUD and identified dental caries in 72% of the cases [ 17 ]. The mean dmft score was 6.2 and dmfs was 22.26, while the mean DMFT score was 2.66 and DMFS was 5.83.…”
Section: Scoping Reviewsupporting
confidence: 84%
“…The presence of enamel hypoplasia can further increase the risk of dental caries. In fact, enamel defects were reported in more than 50% of the cohort examined by Ballikaya et al, 2021, and in the patient reported by Fukushima et al, 1986 and in our patient [ 17 , 20 ].…”
Section: Scoping Reviewsupporting
confidence: 62%
See 3 more Smart Citations